2012
DOI: 10.2217/epi.11.106
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Cell DNA Methylation, Inflammation, Lung Function and Wheezing in Children with Asthma

Abstract: Aims DNA methylation is increasingly proposed as a mechanism for underlying asthma-related inflammation. However, epigenetic studies are constrained by uncertainties on whether samples that can be easily collected in human individuals can provide informative results. Methods Two nasal cell DNA samples were collected on different days by nasal brushings from 35 asthmatic children aged between 8 and 11 years old. We correlated DNA methylation of IL-6, iNOS, Alu and LINE-1 with fractional exhaled nitric oxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 46 publications
(65 reference statements)
2
65
0
Order By: Relevance
“…The nasal epithelium resembles the airway epithelium morphologically, and smoking-related gene expression as well as histological changes, such as mucus production, are similar in nasal and airway epithelial cells (13,19,36). In airway diseases such as asthma, previous studies have demonstrated that DNA methylation changes in NECs from asthmatic children were associated with disease parameters in this population (1), suggesting that epigenetic modification in NECs can reflect changes in the lower airways. In addition, whether and to what extent smoking cessation would be able to revert these epigenetic effects are unclear.…”
Section: Discussionmentioning
confidence: 89%
“…The nasal epithelium resembles the airway epithelium morphologically, and smoking-related gene expression as well as histological changes, such as mucus production, are similar in nasal and airway epithelial cells (13,19,36). In airway diseases such as asthma, previous studies have demonstrated that DNA methylation changes in NECs from asthmatic children were associated with disease parameters in this population (1), suggesting that epigenetic modification in NECs can reflect changes in the lower airways. In addition, whether and to what extent smoking cessation would be able to revert these epigenetic effects are unclear.…”
Section: Discussionmentioning
confidence: 89%
“…DNA methylation is considered the major epigenetic modification in mammalian genomes and is known to have profound effects on gene expression (17). It has been proposed that the expression and responsiveness of several inflammatory mediators are programmed through epigenetic mechanisms, such as DNA methylation (18)(19)(20). Recently, DNA methylation of the IFNG gene, which encodes interferon gamma, was suggested to contribute to differential gene transcription and protein levels of this cytokine in periapical granulomas and radicular cysts (16).…”
mentioning
confidence: 99%
“…This latter study emphasises the importance of careful selection of clinical parameters used in the association study. A more recent study of DNA methylation in nasal cells from 35 asthmatic children aged 8-11 years identified an inverse association of FeNO and promoter methylation of both Il6 and iNOS [65]. Data from two independent pregnancy cohorts in Spain (discovery and validation) showed that DNA hypomethylation in Alox12 in peripheral blood of children was associated with a higher risk of persistent wheezing at age 4 years [62].…”
Section: Dna Methylation and Asthma: Human Studiesmentioning
confidence: 98%
“…While animal studies have begun to decipher the role of epigenetic regulation of gene expression associated with the development of allergic airway disease in the lung, several recent publications in human cohorts have examined DNA methylation in cells outside of the lung: peripheral blood [62], buccal cells [63,64] and nasal cells [65]. These early studies have only demonstrated statistical association of DNA methylation and specific exposure or asthma phenotype, but have not elucidated the role of DNA methylation in the control of gene expression in human asthma.…”
Section: Dna Methylation and Asthma: Human Studiesmentioning
confidence: 99%